A Comparative study to Evaluate the Efficacy of Supervised Exercise Program and Cyriax Physiotherapy on Pain and Function in Lateral Epicondylitis - Gouri Kalaskar; Pratik Phansopkar (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Lateral epicondylitis is a musculotendinous degenerative disease of the extensors originthat occurs at the humerus lateral epicondyle. Various methodologies of treatment are utilized in theboard of lateral epicondylitis.Objectives: The study will investigate the efficacy of the supervised exercise programme and cyriaxphysiotherapy on the refinement of pain and the functional within Lateral epicondylitis patients.Methods: Participants (n=30) with Lateral Epicondylitis (tennis elbow) shall be recruited to participatein a comparative experimental study. Subjects will be randomized 1:1 to either (1) Supervised ExerciseProgramme group, or (2) Cyriax Physiotherapy group. Over a 4-week time period, a 3 times in weekfor the total of 12 sessions, subjects in supervised exercise programme group will receive the ExtensorCarpi Radialis Brevis muscle’s static stretching along with the wrist extensor’s eccentric strengtheningand Ultrasound. While those in group of cyriax physiotherapy will receive transverse deep frictionmassage for the time of 10 min instantly amid by Mill’s manipulation/manoeuvre and Ultrasound. Thestudy will be conclude at the 4 weeks.Discussion: Effectiveness of the interventions on the pain and the functional improvement will beassessed by VAS (visual analogue scale) and the Tennis Elbow Function Scale (TEFS) respectively. Thefindings of the study will greatly contribute for the evidence on the utilization of the supervised exerciseprogramme and therefore the cyriax physiotherapy in tennis elbow condition.Conclusion: After the statistical analysis of the results, final statements regarding the conclusion ofwhich treatment approaches is effective will be made.